Effects of leg stiffness regulated by different landing styles on vertical drop jump performance - You, C.-H.; Huang, C.-H. (Journal of Human Kinetics, 2022)
The purpose of this study was to investigate the effects of stiffness regulated by landing styles on drop jump performance. Twenty-four male lacrosse athletes performed drop jumps with stiff (ST), self-selected (SS), and soft (SF) landing from a 0.42 m box. Leg stiffness, ground contact time, depth, jump height, maximum ground reaction force (GRF), GRF at the start of the propulsive phase, mean power, peak power, and the reactive strength index (RSI) were calculated. The results showed that jump height and the RSI had strong correlations to power production in all drop jump styles. Power would be a key factor to overall athletic performance. Repeated measures ANOVA showed significant differences (p < 0.05) in all variables among the three styles. Drop jumps with SS landing had comparable jump height to drop jumps with SF landing and power output to drop jumps with ST landing. Drop jumps with ST landing had significantly lower jump height, but higher GRF, power, and the RSI compared to drop jumps with SF landing. In drop jump testing, drop jumps with SS landing should be used if power and jump height were the major concerns; if the RSI was the major concern, drop jumps with ST landing should be used. Training with drop jumps, one of the main objectives should be increasing power output due to its significant correlation to jump height and the RSI in all conditions.